Improving stability in developing nations through automation 2006 : a proceedings volume from the IFAC Conference on Supplemental Ways for Improving International Stability through Automation ISA '06, 15-17 June 2006, Prishtina, Kosovo /: a proceedings volume from the IFAC Conference on Supplemental Ways for Improving International Stability through Automation ISA '06, 15-17 June 2006, Prishtina, Kosovo. (2007) - Unknown
No abstract available